2018 IEEE International Conference on Robotics and Automation (ICRA) 2018
DOI: 10.1109/icra.2018.8461194
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Human Teachers to Teach Robot Learners

Abstract: Using Programming by Demonstration to teach robot learners generalisable skills relies on having effective human teachers. This paper aims to address two problems commonly observed in demonstration data sets that arise due to poor teaching strategies; undemonstrated states and ambiguous demonstrations. Overcoming these issues through the use of visual feedback and simple heuristic rules is investigated as a potential way of training novice users to more effectively teach robot learners to generalise a task. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…The effectiveness of this framework as a means of helping novices during LfD is then shown in two experiments with novice users, extending the work presented in (Sena et al, 2018). It is shown in these validation experiments that the evaluation and feedback tools derived from the proposed framework allow for improving teaching performance, in the order of a 180% improvement relative to unguided conditions.…”
Section: Introductionmentioning
confidence: 66%
“…The effectiveness of this framework as a means of helping novices during LfD is then shown in two experiments with novice users, extending the work presented in (Sena et al, 2018). It is shown in these validation experiments that the evaluation and feedback tools derived from the proposed framework allow for improving teaching performance, in the order of a 180% improvement relative to unguided conditions.…”
Section: Introductionmentioning
confidence: 66%
“…Defining a "good" demonstration is a difficult task. There are existing attempts to measure "goodness" by coverage in case of free space motions Sena et al (2018), but for incontact tasks there exists no current work. In the experiments we simply explained the demonstrators how an informative demonstrations should be performed-the development of a general metric of informativeness for compliant motion demonstrations is outside the scope of this paper and an interesting direction for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Fryer and Boyee (2016) observed that while it is clear that teachers are able to play a supportive role, studies have yet to examine the teacher's influence on students' motivation in compulsory learning contexts. Other factor according may be the teacher's lack of prior experience (novice) (Sena et al, 2018); and lack of preparation and confidence (Savitz et al, 2019). On the contrary, the ADM students observed that their teachers moderately show appropriate behavior even during unguarded moments and applies knowledge on social learning in dealing with them.…”
Section: Level Of Implementation Of Alternative Delivery Mode (Adm) When Analyzed In Terms Of Social Regard For Learningmentioning
confidence: 99%